Altitude and excess mortality during COVID-19 pandemic in Peru - Quevedo-Ramirez, Andres (2020)
We have read with interest the short communication published by Segovia-Juarez et al., 2020 in Respiratory Physiology & Neurobiology establishing that high altitude reduces the infection rate of COVID-19 but not the case fatality rate in the Peruvian setting. We support this hypothesis, however there could be an important number of under registered deaths on account of a low rate of diagnostic tests performed per inhabitant and mostly in symptomatic patients (Pasquariello and Stranges, 2020).